WADY WRODZONEHeterotaxy syndrome in a patient with congenital thoracic duct anomaly and pericardial defect – a case report - Kwaśniak, Ewelina; Juściński, Jacek; Haponiuk, Ireneusz; Chojnicki, Maciej; Jaworski, Radosław; Steffek, Mariusz; Zabolska, Irena; Mozol, Krzysztof; Zieliński, Jacek; Gierat-Haponiuk, Katarzyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
The presented case of a patient with heterotaxy syndrome (isomerism of the right atrium) and malalignment ventricular septal defect, partial anomalous pulmonary venous connection, left superior vena cava, and congenital defect of the pericardium shows the difficulties caused by abnormal symmetry and location of organs in the chest. The anatomy of the thoracic duct was not typical. The preparation of the LSVC and cannulation for the CPB caused chylothorax resistant to medical treatment and requiring a thoracotomy. These malformations may pose a significant surgical challenge. The treatment and postoperative management bear a higher risk and the results are worse than those without heterotaxy syndrome.